Tweenagers' clothing purchase behaviors - Anadia, Arvie Joy F.; Bantang, Joanne Reandelar (2006.)
This study aims to examine tweenagers' clothing consumption based on their purchasing motivations, store/brand selection, criteria, shopping frequency, and clothing expenditures. A survey design was used for this study and was done through structured interviews. The data were gathered from randomly selected tweenagers from an urban private school. The sample respondents were composed of 40 tweenagers from Grades Three to Six from the elementary level to represent children between ages eight to 12. Based on the responses gathered, the purchasing motivations considered by tweenagers are: recreation, aesthetic expression, image enhancement, recognition, conformity, fashion expression and sexual attraction. Recreation is the top purchasing motivation considered by tweenagers. Tweenagers enjoy shopping for clothing and that it puts them in good mood. The store/brand selection criteria of tweenagers are: store display, price, product variety/availability, customer service/store image, and store environment. Store display is the top store/brand collection criterion of tweenagers. The visual image of the store is very important to capture the tweenagers' attention to draw them into the store. When male and female tweenagers' shopping frequencies and clothing expenditures were compared, the results show that they shop and spend almost the same amount in clothing. Male tweenagers shop for clothes in an average of 1.45 times a year with an average of Php 175.00 in every purchase transaction. Female tweenagers, on the other hand, shop at 1.70 times a year with an average of Php 160.00 in every purchase transaction.
Thesis (BSHome Economics)--University of the Philippines Diliman.
Keywords: Child consumers -- Philippines; Consumer behavior -- Philippines